IMPLIKASI PEMILIHAN KEPALA DAERAH LANGSUNG TERHADAP MEKANISME HUBUNGAN KERJA BARU KEPALA DAERAH DAN DPRD - Anwar, Anwar (Jurnal Konstitusi, 2010)
This study is intended to understand and analyze the implications of the direct local head election on the work relation between the new local head and the local parliament in establishing local regulations and local budget, and the  monitoring on  the local government in general and, especially the mayor of Malang made by the local parliament. Therefore, the approach employed was a normative approach which was supported by sociological approach. Based pm the results and analyses made, it is known that the relation between the local parliament and the local head merely gives grammatical implication in establishing local regulations, and in making the local budget, the role of the local head is more dominant, while in terms of monitoring made by the local parliament, it is not as strong as before or when the local head was elected through the mechanism of local parliament in accordance with the law no. 22. in the year of 1999.